Source code optimizer using local optimization approach for java based generic code clone detection - Ikhwan Muhammad, Hillmee (2019)
Source code optimization techniques is a technique that is widely used by many researchers and programmers to enhance a software system. It is applied for enhancements especially in terms of performance, time execution, optimizing size of code etc. There are three main available approaches for source code optimization, that is Local Optimization, Global Optimization, and Inter-Procedural Optimization. In addition, this research aims to improve the Generic Code Clone Detection (GCCD) model. GCCD tool is a prototype which is used for detecting code clones. Before enhancing the GCCD model with source code optimization, this research will study about multiple code optimization techniques, its approaches and also the overall structure and processes of GCCD model in order to apply code optimization as part of the process in the GCCD model. Besides that, this research focuses only on the local optimization approach. To obtain the results, datasets from the Bellon’s benchmark for Java will be used for evaluation purposes. There are four (4) steps in the method used in this research, first step is to review the GCCD model and its functions in order to understand its processes and how the model works. Second step is to review code optimization techniques. Third step is to apply code optimization technique as part of the process in GCCD model. The fourth step is to compare the enhanced and original version of the GCCD prototype tool as an evaluation. As a result of this research, an enhanced version of the GCCD prototype is created by implementing and integrating code optimization processes into the GCCD model which will aid the prototype tool to detect better quality code clones. As a conclusion, the improved and enhanced GCCD prototype tool will run in accordance with its original functions without having to change its expected output but can be executed with a better performance.